Algorithms of Classification of Mass Problems of Production Subject Domains - Malakhov, Eugene; Shchelkonogov, Denys; Mezhuyev, Vitaliy (ACM Digital Library, 2019)
This paper develops the algorithms for classification of mass problems of production subject domains. The criteria of the efficiency of control of productions subject domains are introduced. The classes of mass problems, trees of the states of production subject domains and operations on them are introduced.